Waveguide Loss Measurement Using the Reflection Spectrum - DONEGAN, JOHN; LU, QIAOYIN; GUO, WEI-HUA (My University, 2008)
A method for waveguide loss measurement purely based on the reflection spectrum is proposed. Using the Fourier series expansion of the single longitudinal mode in the reflection spectrum, the ratio between the second and first harmonics gives the round-trip loss even when the reflection coefficient of the launching optical field directly reflected by the waveguide facet is unknown. The internal loss of a Fabry?Perot laser diode was measured by the proposed method with results which compare well with those estimated from the amplified spontaneous emission spectrum.
PUBLISHED
Keywords: Amplified spontaneous emission (ASE), Fourier series expansion, reflection spectrum, waveguide loss.